'Come share my world' of 'madness': a systematic review of clinical, diagnostic and therapeutic aspects of folie à deux. (17th August 2020) - Menculini, Giulia; Balducci, Pierfrancesco Maria; Moretti, Patrizia; Tortorella, Alfonso
Abstract: Folie à deux, also known as shared psychotic disorder, shows intrinsic differences when compared to other psychiatric disorders. Literature about this condition is scanty and findings about its clinical correlates are not univocal. The present systematic review aimed at critically summarizing the existing evidence about folie à deux, also focussing on psychopathological, diagnostic and treatment features. The electronic databases PUBMED, Web of Science and Scopus were systematically searched according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. Articles reporting original data about socio-demographic, aetiological, clinical, diagnostic and treatment features of folie à deux, providing information about both primaries and secondaries, were included. Risk of bias was evaluated using the Critical Appraisal Skills Programme (CASP) instruments. The initial search yielded 834 records. After the screening process only 9 papers were deemed eligible for inclusion in the review. Folie à deux emerged to be a heterogeneous condition with a complex etiopathogenesis. The clinical presentation of the disorder included a multi-facet aspect, going beyond the classical description mainly focussed on delusions and possibly explaining conflicting outcomes of different treatments. Diagnostic categories appear to be often reductive and the need for a dimensional approach capable of global reliability emerged.